PERILAKU SOSIAL MASYARAKAT “SEDEKAH KAMPUNG” PERSPEKTIF PENDIDIKAN AQIDAH ISLAM - SULASTRI, DEKA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
Society in this world has many cultures, one of the components of culture is value. Value is a reference or reference that is held as a guideline for the behavior of every member of society or a particular cultural group. For an anthropologist, the term